A study of voluntary welfare agencies' responses to the phenomenon of squatting by Coloured people in Cape Town - Taylor, Carla (Department of Social Development, 2016)
The questions addressed in this research were: (a) to what extent had voluntary welfare agencies in Greater Cape Town been involved during 1982 in work concerning Coloured squatting, and (b) what opinions were held by the agencies concerning aspects of intervention in Coloured squatting. A brief background was given on squatting and on the involvement of various sectors of society in the problem of the Coloured housing shortage in Greater Cape Town. The method of descriptive inquiry was employed. All voluntary social welfare agencies operating in Greater Cape Town and registered under the National Welfare Act and/or the Fund-Raising Act as at 30 September 1982 were listed. All (that is the total universe except for three whose addresses were not on record) were approached by means of a mailed questionnaire containing both closed and open-ended questions on the subject of agency involvement in Coloured squatting and agency opinion on aspects of intervention. Anonymity was guaranteed and respondents were invited to state reasons (if any) for being unable to respond or preferring not to respond to the questions. Forty per cent (114) of the agencies had replied by due date. These constituted a self-selected sample which was, therefore, not representative of the original universe. It was, however, deliberately invited as constituting a new universe comprising the respondent agencies, and was so interpreted in the analysis and conclusions. Analysis of the data revealed that 12 of the 114 agencies that had returned the questionnaire had been actively involved in intervention with Coloured squatters. Of these, only three had responded on a level beyond that of counselling or assisting materially in cases of individual need. Social workers had been involved in work related to Coloured squatting in four of the agencies. Sixteen of the 114 respondent agencies had answered none of the opinion questions, and had indicated that they were not sufficiently informed on the subject to be able to express an opinion. Many others had answered some, but not all questions. The inquiry had been so designed that the extent and nature of this particular response was itself a source of data. Comparison of responses from agencies serving Coloured clients and those not serving Coloured clients revealed differences in the opinions of the two groups. Specifically, these were related to the types of intervention advocated, the categories of actors proposed for involvement in both intervention and co-ordination of intervention, and the combinations of actors chosen for intervention. The actual roles envisaged for each category varied within the two groups of agencies. The most agreed-upon aspects were the need for intervention and co-ordination, and the preference for involvement of various actors in co-operation with one another. The research employed both quantitative and qualitative analysis.